Psychosocial health and activities during the COVID-19 pandemic. - Göktaş, Ayşe; Varlı, Murat (Work, 2023)
BACKGROUND: The COVID-19 pandemic has become a major cause of stress at work. OBJECTIVE: To examine the effect of self-management and self-control skills on perceived stress of employees in the COVID-19 period. METHODS: The study's self-administered survey included demographics and the Perceived Stress Scale (PSS) and Self-Control and Self-Management Scale (SCMS). Associations with PSS were determined using a multiple variable linear regression analysis. RESULTS: Scores for stress (28.45±7.82) and self-management (55.73±12.15) were moderate for employees. Of the 181 employees, 41.43% had a mild, 52.48% had moderate, and 6.07% had severe stress levels. Stress was significantly associated with lower self-management level. A negative relation was found between SCMS and PSS (p = 0.000, r = –0.320). Employees with high self-management skills had low stress levels. Employees also reported negative changes to physical activity, income and sleep. Gender, occupation, income category, compliance with COVID-related rules and self-management were associated with levels of stress (p < 0.05). The regression model explained 24.8% of the variance in stress perception (R2 = 0.248, F = 11.452, p = 0.000). Multiple linear regression analysis showed gender (β = 5.089, 95% CI: 2.820 to 7.358, p = 0.000) compliance with COVID-related rules (β = 2.274, CI: 0.066 to 4.483, p = 0.044), a decrease in income (β = 2.051, CI: –0.64 to 4.166, p = 0.057) and self-management (β = -0.173, CI: –0.258 to –0.087, p = 0.000) were significantly associated with lower scores in the stress perception. CONCLUSION: Self-control and self-management were associated with a decline in mental health. Health-promotion strategies directed at adopting or maintaining positive self-control and self-management-related behaviors should be utilized to address increases in psychological distress during the COVID-19 pandemic.